STUDI KASUS PENGOLAHAN HIDANGAN BERBAHAN DASA IKAN DENGAN TEKNIK PANAS KERING DAN PANAS BASAH DI HOTEL MERCURE SURABAYA GRAND MIRAMA - Fatah, Dwitiya Paramita Acintya Fatah; Any Sutiadiningsih; Mauren Gita Miranti (Jurnal Sains Boga, 2025)
Heat-based processing techniques, such as dry heat (e.g., baking and frying) and moist heat (e.g., steaming and boiling), have been widely applied in the fish-based food industry. Dry heat methods provide as crispy texture and distintive aroma resulting from the Maillard reaction, while moist heat techniques tend to preserve the water content and nutrients of the fish. Although both mtehods have their advantages, they also face various challenges, such as nutrient degradation, texture changes, and consumer acceptance of the final product. In the research, observations were conducted at the Kitchen Hotel Mercure Surabaya Grand Mirama, aiming to identify various types of fish-based dishes according to their cooking techniques (dry and moist heat). This study also aimed to understan the stages involved in preparing the fish, starting from the selection, cleaning, and cutting processes as required. The research methodology employed included observation, interviews, document studies, and the drawing of conclusions from the collected data. The type of research conducted involved qualitative descriptibe data based on the observations and interview results, reported with actual occurrenses. Data collection techniques involved using instruments for observation grid and interviews. The findings indicate that the choice of processing techniques significantly affects the texture, flavor, and nutritional value of the dishes. Proper preparations of ingredients and spices is crucial in the processing of fish-based dishes, and the preparation of spices varies depending on the chosen processing technique. It can be concluded that the processing technique influences the texture, flavor and nutritional value of the food. The quality of the dishes highly depends on the selection of fresh fish.